Implementasi Model Pembelajaran Berbasis Masalah (Problem Based Learning) Pada Pendidikan Agama Islam (PAI) di Sekolah Dasar - Sari, Novia Permata; Magdalena, Ina; Putri, Raafiza; Syaputri, Sekartini Rikawan (ANWARUL, 2022)
So far, the learning system that occurs in elementary schools is still filled with a world view which states that information is a set of realities that must be remembered. In addition, most of the learning space situation is still centered on the instructor (focused on educators or teachers) as a source of basic information, and the use of speaking techniques as the main decision of the teaching and learning system. Such a learning situation does not include students in making questions. To foster a teaching and learning environment that can foster courage, mentality, and inventive and innovative behavior, it is very important to have a relationship between the parts of the training, such as instructors, students, educational plans, apparatus (learning media) and learning assets, materials, techniques , and assessment tools work together to create useful learning measures, the Problem Based Learning model is the best decision in today's learning. The problem is how to apply the issue-based learning model in PAI learning in elementary schools?